PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, PERTUMBUHAN PENJUALAN, KEPEMILIKAN MANAJERIAL TERHADAP PENGHINDARAN PAJAK (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR CONSUMER NON CYCLICAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2021) - Aldha Nava Pratiwi; Listyorini Wahyu Widati (Jurnal Riset Akuntansi Politala, 2024)
Taxes are a source of income for the state, while for companies taxes are a burden that will reduce net profits. The difference between the interests of affiliates who want large tax revenues is always at odds with the interests of corporate investors who want possible annual tax payments. Differences in perceptions regarding taxes as a source of income for the state are a factor causing non-optimal tax payments. The aim of the research is to analyze the influence of SIZE, AGE, SG and KM on ETR. Non-cyclical consumer companies were listed on the Indonesia Stock Exchange between 2018 – 2021 with a total of 9 samples collected. Multiple linear regression analysis for data verification. The research results show that SIZE + is significant ETR, while AGE and SG - are significant ETR, but KM + is significant ETR.